FAKTOR-FAKTOR YANG MEMPENGARUHI INFORMASI AKUNTANSI PADA UMKM DI KOTA MEDAN - Handriyani Dwilita (Jurnal Akuntansi Bisnis dan Publik, 2020)
Small and Medium Enterprises (SME) is a type of business that can be managed directly by the community or family, SME is very influential for a country’s economy, which one is to reduce unemployement. Therefore SME must continue to develop overtime, one of the things that is very important for SME is to develop their business is accounting information (financial statements). This research is a type of descriptive study of SME in the city of Medan which is being guided by the Dinas Koperasi. The study aims to provide an overview of the characteristics of SME, as well as an understanding of the application of accounting and the nature of leadership that tends to be used, but also given an overview of SME in terms of demographics. The results of the study revealed that based on gender, the majority of SME entrepreneurs were women. The dominant tribe is Javanese and Batak. Most of the business sectors that are undertaken are trading businesses. Most SME’s entrepreneurs have recorded their business activities, but they are still in a very simple form. Only how many people carry out the accounting process convey the final accounting information, namely the Financial Statements. SME have followed and understood the accounting training material that has been conducted by the Dinas Koperasi. The types of leadership of SME tend to be Participation and Consideration.